Effect of Salbutamol on Growth Performances of Parrot cichild - Sirimongkolvorakul, Sunisa; Bunnajirakul, Sumrarn; Thongdet, Ekthida; Sornphu, Tanasid (Journal of Mahanakorn Veterinary Medicine, 2019)
β-agonists has been well documented for the ability to increase growth rate as well as improve feed efficiency in various species. However, there is limited information on use in ornamental fishes. The present study aimed to investigate the effect of salbutamol in fish feed. A total of 24 healthy Parrot cichlid were fed with test diets containing 0.0, 0.5, 1.0 and 2.0 ppm of salbutamol per gram of fish diet, respectively, for 28 days. The results showed that salbutamol had varying effects on growth parameters and body length ranged from 5.06±0.54 to 2.39±0.16 gram in weight and 0.46±0.03 to 0.38±0.04 in length. Among those, fish fed diet containing 0.5 ppm of salbutamol were improved growth parameters as well as the body length (4.72±0.09 g.; 0.50±0.02 cm.). Whereas, fish fed diets contained 0.0, 1.0 and 2.0 ppm was not markedly influenced by salbutamol supplementation. However, feeding salbutamol up to 28 days have limited effects on muscle growth may be due to physiological regulation. This study indicates that dietary supplemented with salbutamol could improve the growth of parrot cichlid. Therefore the information could be applied to the use of salbutamol as feed additive nevertheless veterinary drug residue could be considered.